The most important challenges facing the Iraqi economyAnd ways to address them - الدليمي بلاسم جميل (Journal of Economics and Administrative Sciences, 2011)
Facing the Iraqi economy, a number of economic challenges that threaten the future of Iraq and the security of economic, political and social, such as poverty, unemployment, inflation and the dilapidated infrastructure and rising production costs and administrative and financial corruption, environmental pollution, water problems and the deterioration of agricultural and industrial production, etc., and over the seriousness of these challenges, they are intertwined and overlapping and growing worse, without the corresponding adoption of state strategies that will develop appropriate solutions and appropriate to resolve those challenges because of concern the subject of security and terrorism, which requires the development of an integrated strategy through which to address these challenges.